Deliberative peace referendums - Levy, Ron (Law teacher); Kong, Hoi L.; O'Flynn, Ian (Oxford comparative constitutionalism., 2021)
eace referendums', which seek to manage conflict between warring groups, are increasingly common. Yet they remain erratic forces--liable as often to aggravate as to resolve tensions. This book argues that, despite their risks, referendums can play useful roles amid armed conflict. Drawing on a distinctive combination of the fields of deliberative democracy, constitutional theory and conflict studies, and relying on comparative examples (eg, from Algeria, Colombia, New Caledonia, Northern Ireland, Papua New Guinea, and South Africa), the book shows how peace referendums can fulfil their promise as genuine tools of conflict management.